Video Games as Foreign Policy Tools: A Comparative Between Japan and Poland - Putu Radar Bahurekso; Sinta Ningrum; Dadang Enjat Munajat (Journal of Law, Politic and Humanities, 2025)
This study examines the role of video games as instruments of foreign policy by comparing Japan and Poland. Utilizing a qualitative comparative analysis, it explores how each country has strategically integrated video games into cultural diplomacy and soft power initiatives. Japan’s "Cool Japan" initiative exemplifies long-term state-supported cultural promotion, highlighted by Prime Minister Shinzo Abe’s appearance as Mario at the 2016 Rio Olympics. Poland, on the other hand, leverages its globally successful The Witcher franchise to enhance its cultural footprint, as demonstrated by Prime Minister Donald Tusk gifting The Witcher 2 to President Barack Obama. By analyzing these cases, this research identifies key policy frameworks, institutional support mechanisms, and socio-political contexts that shape the use of video games as tools for national branding and international relations. The findings suggest that government-backed gaming initiatives can significantly influence global perceptions and offer valuable lessons for other nations seeking to utilize their gaming industries for diplomatic and economic gains.